TMEM121 Protein Is a RegulatIon Factor in the Proliferation Activity of the Adrenocortical stem/Progenitor Cells (Medico Legal Update, 2021)
Several studies have identified adrenocortical sub-population cells located in the capsule/sub-capsular area,carrying the aspects of stem/progenitor cells. We previously recognized a novel protein (Tmem121) highlyexpressed in in this sub capsular area and also highly co-localised with Ki67 in this area. The suggestionof these previous studies was considered to clone and transfect Tmem121 into adrenocortical stem/progenitor cells studying the proliferation changes in the transfected cells. Adrenocortical stem/progenitorcells were isolated and cultivated in vitro. The cells were previously isolated and prepared for testing theeffect of Tmem121 after three months of in vitro cultivation. Specific primers were used to detect andamplified the coding sequence of the TMEM121 using RT-PCR followed by cloning into pIRES2-ERFPvector. Immunocytofluorescent tests were carried out to detect the forced expression of TMEM121 intothese cells. Real time PCR assays were followed with specific primers to detect the synchronization ofTmem121 expression with two proliferation markers Ki67 and proliferating cell nuclear antigen (PCNA).Immunocytofluorescent tests results showed a significant expression of TMEM121 into these cells. Realtime PCR results showed a significant increase in the expression of both proliferation markers Ki67 and(PCNA). These results suggested a propagating effect of TMEM121 to the adrenocortical stem/progenitorcells.